Integration Of Overall Equipment Effectiveness (Oee) And Reliability For Measuring Machine Effectiveness - Samat, Hasnida Ab (2010)

(untitled)
The Murphy’s Law that goes “Things will go wrong in any given situation, if given a chance” is best represents the importance of maintenance system. Maintenance is conducted with aims to eliminate failures, reduce machine downtime, minimize manufacturing cost and improve production rate. Maintenance is one of the functions in asset management, and it covers the proper use of resources like human, information, materials, and capital to make certain that equipment, machinery, buildings and plant are repaired, replaced, adjusted, and modified to allow it to operate at its designated performance and in specified lifetime. Therefore maintenance should be conducted effectively and its performance should be measured from time to time.